Effects of selected peripheral rewarming methods on vital signs among patients post coronary artery bypass graft (CABG) - Avellona, Mylene K.
This research proposed to compare the effects of cellophane, overhead heat lamp and blanketroll as peripheral rewarming methods on the vital signs of adult patients who underwent coronary artery bypass graft. It also attempted to find out the confounding effects of the physical and surgical factors on the vital signs during rewarming. The factors that influence the selection of peripheral rewarming methods as perceived acceptability and ease of administration by nurse care provider were identified.Specifically, the study answered the following questions:1. Is there a significant difference among the three rewarming methods on the mean gain score of: a.) body temperature b.) blood pressure c.) heart rate d.) heart rhythm at a.) 30 mins. post-operatively b.) 60 mins. post-operatively c.) 120 mins. post-operatively d.) 240 mins. post-operatively?2) Is there significant relationship among physical factors such as: a.) age b.) sex c.) BSA d.) status of hydration; and the vital signs such as: a.) body temperature b.) blood pressure c.) heart rate d.) heart rhythm at a.) 5 mins. post-operatively d.) 30 mins. post-operatively c.) 60 mins. post-operatively d.) 120 mins. post-operatively e.) 240 mins. post-operatively?3) Is there a significant relationship among surgical factors such as: a.) surgical procedures done b.) total bypass time c.) degree of hypothermia intraoperatively d.) length of surgery e.) temperature at end of surgery and the vital signs at a.) 5 mins. post-operatively b.) 30 mins. post-operatively c.) 60 mins. post-operatively d.) 120 mins. post-operatively e.) 240 mins. post-operatively?4) What factors influence the selection of peripheral rewarming methods?a.) Perceived acceptability of the nurse care providerb.) Perceived ease of administration by the nurse care providA total of 85 subjects were included in the study, 5 subjects were dropped out due to insertion of Intraaortic Balloon Pump (IABP) post-operatively. Subjects were randomly assigned to those treatment groups. Experimental group 1 was treated with cellophane + blanketroll, experimental group 2 were treated with overhead heat lamp + blanketroll, and a control group treated with blanketroll alone. The three groups were compared as to their effect on vital signs; temperature, blood pressure, heart rate, and heart rhythm during different time intervals post-operatively. The treatment methods were initiated once patient was noted to be hypothermic, and were stopped once the patient's temperature normalized. Vital signs of subjects were taken and recorded 5 mins, 30 mins, 60 mins, and 120 mins, and 240 mins. post-operatively?Other pertinent data as total bypass time, surgical procedure done, length of surgery, temperature at end of surgery, degree of hypothermia intraoperatively were taken from the operative record.The findings of the study showed the following results:1. The use of blanketroll significantly differ in temperature compared with the use of cellophane + blanketroll at 30 mins. and 60 mins. post-operatively. The higher mean indicated that blanketroll remained to be the most effective method to rewarm.2. The use of overhead heat lamp + blanketroll did not differ significantly with the two other methods, however, a mean temperature gain of 0.44?C 60 mins. post-operatively indicated some degree of heat gain.3. Hydration was significantly related to temperature at 5 mins. and 30 mins. post-operatively. Poorly hydrated patients had greater degree of temperature afterdrop and slower to rewarm than those who were well hydrated.